Estudo de pré-tratamento e hidrólise com ácidos orgânicos no isolamento de fibras de celulose - Silva , Cleonice Gonçalves (2019)
The agro industrial residues have been used for fiber production, due to its high cellulosic content, abundance in nature and low cost. The application of these raw materials as reinforcing agent for polymer matrices has attracted considerable attention as these composites generally exhibit superior thermal, mechanical and barrier properties over pure polymer or conventional composites. In this context, the present study aimed to study the extraction of ground coffee husk fibers in the form of micro/nanocrystalline cellulose particles, using different pre-treatments and subsequent hydrolysis with organic acids as an option to replace the method with sulfuric acid. For this purpose, the pre-treatments were compared in autoclave (121 ° C for 30min with 5% NaOH), microwave (3 cycles with 100% potency and 5 min with 5% NaOH) and as control stirring (100 ° C for 4 h with 5% NaOH). After the pre-treatments the samples were bleached in acetate solution and aqueous sodium chlorite and also analyzed. The result of chemical composition showed that pre-treatment in autoclave was the one that extracted the largest amount of non-cellulosic components from the shells, being thus chosen for the step of hydrolysis. The sample obtained in pretreatment by autoclave and bleached was then used in the studies (w / v) at 80 ° C for 40 min and, with sulfuric acid (S) as the control, at 50% (w / v) 40 ° C for 40min. All samples obtained in the hydrolysis step were analyzed for chemical composition and morphology. The results of hydrolysis using the organic acids obtained smaller particles, remaining in structure of micro fibers, because these reagents were efficient in the removal of amorphous components. The autoclave pre-treatment proved to be promising for the process of reducing cellulose particle fibers. The citric acid showed to be very promising in the process, since it was the one that presented better decrease of Mv and GP as well as better exposure of the cellulose in the results of chemical composition.